Conservative preparation of curved root canals using novel nickel-titanium instruments: influence of operator experience - Reem M. Barakat; Rahaf A. Almohareb (Heliyon, 2022)
Background: Nickel-titanium (NiTi) instrumentation systems allow predictable dental root canal treatment. Novel systems promoting conservative preparation are constantly introduced into the market. Therefore, this study aimed to explore how operator experience would influence the performance using a new system – Race Evo- in preparation of curved root canals. Methods: Three groups of participants, with no previous experience with Race Evo, were compared: Third-year dental students, general dental practitioners (GPs), and endodontists. Each participant was asked to prepare 3 simulated resin blocks. Preparation time, the occurrence of procedural errors, and canal deviation were measured. Results: Endodontists prepared the canals with significantly fewer procedural errors (p = 0.027), and in less time than students (p < 0.001) and GPs (p = 0.019). However, there was no significant difference in performance between undergraduate students and GPs. In fact, endodontists and students alike prepared the canal with less deviation compared to GPs (p = 0.006 and p = 0.002). Conclusion: Proficiency in instrumenting curved canals with a new conservative NiTi system was not influenced by experience related to that of the general dental practitioner, but required more specialized experience in root canal treatment. Regardless of experience level, a learning period was still necessary.